Control de inventario de la empresa “auto grupo Lozada” en el periodo 2020-2021 - Aguilar Llaguno, Linda Gabriela (2022)
Currently, globalization and the high level of competition have led many business owners to seek new development paths to reach a stage of prosperity and economic stability. quality and agility in the processes to achieve maximum economic results. By means of a permanent merchandise inventory control system, the owner of the Auto Grupo Lozada company will be able to know in reality the rotation of each one of the products, they will also be able to know which are the most requested and based on what criteria to carry out a new request, in such a way that specific strategies can be extracted to take advantage of said situation; In the same way, it will indicate the products that are least sold so that techniques can be established so that their demand increases or simply that the company stops investing in that type of product since they do not help in the profitability of the business. The company must carry out inventory continuously in order to avoid physical and therefore monetary losses that affect its performance. This case study describes the problem that Auto Grupo Lozada is going through, the objectives that are expected to be achieved by applying inventory control and the justification for the project, as well as containing theoretical foundations that cover the main aspects of the inventory and the management system. internal control and the methodology and techniques used to perform this analysis, the results of the information obtained were also analyzed and interpreted, and the conclusions are described.